Trends of Government Communications in Digital Public Sphere of Russia: 2011-2020 - O. G. Filatova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2020)
The paper presents the results of two studies conducted in the early 2010s and early 2020th, which allow us to identify trends in the development of state communications in the digital public sphere of Russia. The studies were carried out on the same series using the same methods with some adjustments. The sites of all Russian public authorities at the federal level, as well as state communications in social media, were analyzed with an interval of 9 years. State communications are understood as communicative relations, the subject of which is the state as a whole, a state institution or a public authority, and which can be labeled as state PR. The subject of state communications is relations regarding the governing of state power. Comparing the results of two studies of state communications in Russia, the author analyzes the changes over the decade and draws conclusions about the active, but ineffective development of such communications that do not allow citizens to actively participate in political decision-making processes, as well as the ambiguous development of the digital public sphere of modern Russia in general. The wide interactive possibilities of modern social media which imply the priority of intermutual communication remain generally unclaimed. Despite the growth of channels, tools, services provided by modern Internet technologies, they are used by public authorities mainly for informational purposes only, without facilitating two-way communication with the population and therefore do not lead to a significant improvement in the image of power.